Types & grammar - Simpson, Kyle (You don't know JS, 2015)
No matter how much experience you have with JavaScript, odds are you don't fully understand the language. As part of the "You Don't Know JS" series, this compact guide explores JavaScript types in greater depth than previous treatments by looking at type coercion problems, demonstrating why types work, and showing you how to take advantage of these features.